Electrochemical and electronic equipment
Patent Information
- Application Number
- JP2026516538
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2026-10-14
AI Technical Summary
【0004】 本願の第1の態様は、正極片を含む電気化学装置を提供する。正極片は、正極活物質層を含み、正極活物質層は、第1正極活物質および第2正極活物質を含む。第1正極活物質は、Ni元素およびMn元素を含み、第2正極活物質は、Ni元素およびCo元素を含む。電気化学装置の放電時の容量電圧微分dQ/dVと電圧Vとの関係曲線は、3.8V以上に少なくとも2つのピークを含む。本願の電気化学装置において、第1正極活物質は、第2正極活物質に対して、電気化学装置の放電時の容量電圧微分dQ/dVと電圧Vとの関係曲線における高電圧領域に特徴的なピークを有し、それにより電気化学装置が高電圧領域において高い可逆放電容量を持つことができ、電気化学装置の高エネルギー密度の要求を満たすことができる。同時に、第1正極活物質が高電圧領域での脱リチウム量が高いため、第2正極活物質が過剰に脱リチウムするリスクを低減でき、それにより第2正極活物質の高温·高電圧での構造安定性を向上させることができる。また、第1正極活物質自身の表面に酸素空孔を有するため、その表面からの酸素発生を抑制することができ、高温·高電圧でも高い構造安定性を維持することができ、それにより電気化学装置のサイクル性能および安全性能を大幅に向上させることができる。
Smart Images

Figure 2026534134000001_ABST
Abstract
Description
[Technical Field]
[0001] This application relates to the field of electrochemical energy storage, and more particularly to electrochemical and electronic devices. [Background technology]
[0002] With the advancement of electrochemical energy storage technologies, the demands on energy density and safety performance of electrochemical devices (e.g., lithium-ion batteries) are increasing. For example, with the growing demand for longer driving ranges in the power battery market, high-nickel ternary materials with high energy density have already become a focus of development. However, as the nickel content increases, the thermal stability of ternary materials deteriorates, reducing the safety of high-nickel ternary materials and thus limiting their widespread application. [Overview of the Initiative] [Problems that the invention aims to solve]
[0003] In view of this, the present invention provides an electrochemical apparatus and an electronic apparatus that meet the requirements for high energy density in electrochemical apparatuses while simultaneously improving the safety of electrochemical apparatuses. [Means for solving the problem]
[0004] A first aspect of the present invention provides an electrochemical apparatus including a positive electrode piece. The positive electrode piece includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes elements Ni and Mn, and the second positive electrode active material includes elements Ni and Co. The relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes at least two peaks above 3.8V. In the electrochemical apparatus of the present invention, the first positive electrode active material has a characteristic peak in the high-voltage region of the relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus, compared to the second positive electrode active material, thereby enabling the electrochemical apparatus to have a high reversible discharge capacity in the high-voltage region and satisfy the requirement for high energy density of the electrochemical apparatus. At the same time, because the first cathode active material exhibits a high amount of delithiation in the high-voltage region, the risk of excessive delithiation of the second cathode active material can be reduced, thereby improving the structural stability of the second cathode active material at high temperatures and high voltages. Furthermore, because the first cathode active material itself has oxygen vacancies on its surface, oxygen generation from its surface can be suppressed, allowing it to maintain high structural stability even at high temperatures and high voltages, thereby significantly improving the cycle performance and safety performance of the electrochemical apparatus.
[0005] In some embodiments, the relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes peaks A and B above 3.8V. Here, the peak position of peak A is in the range of 3.8V to 4.1V, and the peak position of peak B is in the range of 4.1V to 4.3V. The peak area of peak A is S A The peak area of peak B is S B Therefore, 0.5 ≤ S B / S A The condition ≤ 1 is satisfied. Here, peak A mainly depends on the second positive electrode active material, and peak B mainly depends on the first positive electrode active material. B / S A This can be used to indirectly represent the mixing ratio of the first positive electrode active material and the second positive electrode active material. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, peak A and peak B are 0.5 ≤ S. B / S ABy satisfying ≦1, the electrochemical device can achieve both excellent cycle performance and safety performance. Further, in some embodiments, 0.5≦S B / S A ≦0.85 is satisfied.
[0006] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V during discharge of the electrochemical device further includes a peak C within the range of 3.5V to 3.7V. Here, the presence of peak C can further increase the discharge capacity of the electrochemical device, thereby further improving the energy density of the electrochemical device.
[0007] In some embodiments, the relationship curve between the capacity-voltage differential dQ / dV and the voltage V during discharge of the electrochemical device includes at least one peak at 4.1V or higher. This indicates that the first positive electrode active material has good reversible capacity in the high voltage region, and can improve the cycle performance and safety performance of the electrochemical device.
[0008] In some embodiments, when the electrochemical device is in a fully discharged state, X-ray diffraction measurement is performed on the positive electrode sheet, and the sheet has a diffraction peak 1 in the range of 43.7° to 44.1°, the peak intensity of diffraction peak 1 is defined as P1, and has a diffraction peak 2 in the range of 44.2° to 44.6°, the peak intensity of diffraction peak 2 is defined as P2, which satisfies 1≦P2 / P1≦6.5. Here, diffraction peak 1 corresponds to the first positive electrode active material, and diffraction peak 2 corresponds to the second positive electrode active material. When P2 / P1 satisfies the above range, the electrochemical device can achieve both excellent cycle performance and safety performance. Further, in some embodiments, 2.3≦P2 / P1≦6.5 is satisfied.
[0009] In some embodiments, the first positive electrode active material further comprises an M1 element, and M1 includes at least one of Na or K. Based on the metal elements other than the Li element and the M1 element in the first positive electrode active material, if the mole percentage of the Ni element in the first positive electrode active material is defined as a1, the mole percentage of the Mn element is defined as b1, and the mole percentage of the M1 element is defined as c1, the relationships 30%≦a1≦70%, 30%≦b1≦70%, and 0.1%≦c1≦15% are satisfied. By doping with the M1 element, the first positive electrode active material has good structural stability at high temperature and high voltage, which can improve the cycle performance and safety performance of the electrochemical device.
[0010] In some embodiments, the second positive electrode active material further comprises an M2 element, and M2 includes at least one of Mn or Al. Based on the metal elements other than the Li element in the second positive electrode active material, if the mole percentage of the Ni element in the second positive electrode active material is defined as a2, the mole percentage of the Co element is defined as b2, and the mole percentage of the M2 element is defined as c2, the relationships 80%≦a2≦98%, 1%≦b2≦19%, and 1%≦c2≦19% are satisfied. The presence of the M2 element can improve the structural stability of the second positive electrode active material at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical device.
[0011] In some embodiments, the first positive electrode active material is secondary particles formed by agglomeration of primary particles. Thereby, the kinetic performance of the electrochemical device can be improved.
[0012] In some embodiments, the average particle size of the first positive electrode active material is 6 μm to 14 μm.
[0013] In some embodiments, the second positive electrode active material is primary particles. Thereby, the structural stability of the second positive electrode active material at high temperature and high voltage can be improved, and thus the cycle performance and safety performance of the electrochemical device can be enhanced.
[0014] In some embodiments, the average particle size of the second positive electrode active material is 3 μm to 10 μm.
[0015] In some embodiments, if the area of the first positive electrode active material in a 127 μm × 34 μm region in the cross-section in the thickness direction of the positive electrode active material layer is S1 and the area of the second positive electrode active material is S2, then the condition 0.5 ≤ S2 / S1 ≤ 1.5 is satisfied. By satisfying the above range for S2 / S1, the electrochemical apparatus can achieve both excellent cycle performance and safety performance. Furthermore, in some embodiments, the condition 0.7 ≤ S2 / S1 ≤ 1.3 is satisfied.
[0016] In some embodiments, the first positive electrode active material has a layered crystalline structure belonging to the R-3m space group. In some embodiments, the first positive electrode active material is Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1 The elements include 0.6≦x1≦1.2, 0.001≦m≦0.15, 0.3≦y1≦0.7, 0.3≦z1≦0.7, 0≦q1≦0.2, and 0≦n1≦0.2, where element M1 includes at least one of Na or K. Element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge. Also, element T1 includes at least one of F, Cl, Br, I, or N.
[0017] In some embodiments, the second positive electrode active material has a layered crystalline structure belonging to the R-3m space group. In some embodiments, the second positive electrode active material is Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2The set of elements includes 0.6≦x2≦1.2, 0.8≦y2≦0.98, 0.01≦z2≦0.19, 0.01≦p≦0.19, 0≦q2≦0.1, and 0≦n2≦0.2, where element M2 includes at least one of Mn or Al. Element R2 includes at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge. And element T2 includes at least one of F, Cl, Br, I, or N.
[0018] A second aspect of the present application further provides an electronic apparatus including the electrochemical apparatus described above. [Brief explanation of the drawing]
[0019] To more clearly explain the technical details of the embodiments of this application, the drawings necessary for describing the embodiments are briefly described below. The drawings described below represent only some embodiments of this application, and it will be clear to those skilled in the art that other embodiments can be derived from these drawings. [Figure 1] The discharge curve of the electrochemical apparatus according to Example 1 of this application is shown. [Figure 2] The relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus according to Embodiment 1 of this application is shown. [Figure 3] This shows a scanning electron microscope (SEM) image of a cross-section of the positive electrode piece according to Example 1 of the present invention. [Figure 4] This shows the X-ray diffraction (XRD) pattern of the positive electrode piece in the complete discharge state of the electrochemical apparatus according to Example 1 of the present application. [Modes for carrying out the invention]
[0020] In the following, the technical details relating to the embodiments of this application will be clearly and sufficiently explained with reference to the drawings of the embodiments. It is clear that the embodiments described are only a selection of the embodiments of this application, and not all embodiments.
[0021] A first aspect of the present application provides an electrochemical apparatus including a positive electrode piece. The positive electrode piece includes a positive electrode active material layer. The positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes elements Ni and Mn, and the second positive electrode active material includes elements Ni and Co. Here, the relationship curve between the capacitance voltage derivative dQ / dV and the voltage V during discharge of the electrochemical apparatus includes two peaks for voltages above 3.8V.
[0022] In the electrochemical apparatus of this invention, the first positive electrode active material has a characteristic peak in the high-voltage region of the relationship curve between the capacitance-voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus, compared to the second positive electrode active material. This allows the electrochemical apparatus to have a high reversible discharge capacity in the high-voltage region, thereby meeting the requirement for high energy density of the electrochemical apparatus. At the same time, because the first positive electrode active material has a high delithiation rate in the high-voltage region, the risk of excessive delithiation of the second positive electrode active material can be reduced, thereby improving the structural stability of the second positive electrode active material at high temperatures and high voltages. Furthermore, because the first positive electrode active material has oxygen vacancies on its surface, oxygen generation from its surface can be suppressed, allowing it to maintain high structural stability even at high temperatures and high voltages, thereby significantly improving the cycle performance and safety performance of the electrochemical apparatus.
[0023] In some embodiments, the relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes peaks A and B above 3.8V. Here, the peak position of peak A is in the range of 3.8V to 4.1V, and the peak position of peak B is in the range of 4.1V to 4.3V. The peak area of peak A is S A The peak area of peak B is S B Therefore, 0.5 ≤ S B / S A The condition ≤ 1 is satisfied. Here, peak A mainly depends on the second positive electrode active material, and peak B mainly depends on the first positive electrode active material. B / S AThis can be used to indirectly represent the mixing ratio of the first positive electrode active material and the second positive electrode active material. By adjusting the relative content of the first positive electrode active material and the second positive electrode active material, peak A and peak B are 0.5 ≤ S. B / S A By satisfying ≤ 1, the electrochemical apparatus can achieve both excellent cycle performance and safety performance. Selectively, S B / S A S is a range consisting of 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any two of the above values. Furthermore, in some embodiments, 0.5 ≤ S B / S A It satisfies ≤ 0.85.
[0024] In some embodiments, the relationship curve between the capacitance-voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes a peak C within the range of 3.5V to 3.7V. Here, the presence of peak C allows for a higher discharge capacity of the electrochemical apparatus, thereby further improving the energy density of the electrochemical apparatus.
[0025] In several embodiments, the relationship curve between the capacitance-voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes at least one peak above 4.1V. This demonstrates that the first positive electrode active material has good reversible capacitance in the high-voltage region, thereby improving the cycle performance and safety performance of the electrochemical apparatus.
[0026] In some embodiments, when the electrochemical apparatus is in a fully discharged state, X-ray diffraction measurements are performed on the positive electrode piece. If diffraction peak 1 is in the range of 43.7° to 44.1°, and the peak intensity of diffraction peak 1 is denoted as P1, and diffraction peak 2 is in the range of 44.2° to 44.6°, and the peak intensity of diffraction peak 2 is denoted as P2, then the condition 1 ≤ P2 / P1 ≤ 6.5 is satisfied. Here, diffraction peak 1 corresponds to the first positive electrode active material, and diffraction peak 2 corresponds to the second positive electrode active material. When P2 / P1 satisfies the above range, the electrochemical apparatus can achieve both excellent cycle performance and safety performance. Selectively, P2 / P1 is in the range of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, or any two of the above values. Furthermore, in some embodiments, the condition 2.3 ≤ P2 / P1 ≤ 6.5 is satisfied. In this case, the cycle performance and safety performance of the electrochemical apparatus are even better.
[0027] In some embodiments, the first positive electrode active material further contains an element M1, where M1 contains at least one of Na or K. Doping with the element M1 gives the first positive electrode active material good structural stability at high temperature and high voltage, thereby improving the cycle performance and safety performance of the electrochemical apparatus.
[0028] In some embodiments, the M1 element is doped into the lithium layer. This better stabilizes the crystal structure of the first cathode active material in a highly delithiated state, thereby improving the cycle performance and safety performance of the electrochemical apparatus.
[0029] In some embodiments, using the metal elements other than Li and M1 in the first positive electrode active material as a reference, if the molar percentage of Ni in the first positive electrode active material is a1, the molar percentage of Mn is b1, and the molar percentage of M1 is c1, then the following conditions are met: 30% ≤ a1 ≤ 70%, 30% ≤ b1 ≤ 70%, and 0.1% ≤ c1 ≤ 15%.
[0030] In some embodiments, the second positive electrode active material further contains an element M2, where M2 contains at least one of Mn or Al. Based on the metal elements other than Li in the second positive electrode active material, if the molar percentage of Ni is a2, the molar percentage of Co is b2, and the molar percentage of M2 is c2, then the following conditions are met: 80% ≤ a2 ≤ 98%, 1% ≤ b2 ≤ 19%, and 1% ≤ c2 ≤ 19%. The presence of the M2 element improves the structural stability of the second positive electrode active material at high temperatures and high voltages, thereby improving the cycle performance and safety performance of the electrochemical apparatus.
[0031] In some embodiments, the first positive electrode active material is secondary particles formed by the aggregation of primary particles. This can improve the dynamic performance of the electrochemical apparatus.
[0032] In some examples, the average particle size of the first positive electrode active material is 6 μm to 14 μm.
[0033] In some embodiments, the second cathode active material is primary particles. This improves the structural stability of the second cathode active material at high temperatures and high voltages, thereby improving the cycle performance and safety performance of the electrochemical apparatus.
[0034] In some examples, the average particle size of the second positive electrode active material is 3 μm to 10 μm.
[0035] In some embodiments, if the area of the first positive electrode active material in a 127 μm × 34 μm region in the cross-section in the thickness direction of the positive electrode active material layer is S1 and the area of the second positive electrode active material is S2, then the condition 0.5 ≤ S2 / S1 ≤ 1.5 is satisfied. This allows the electrochemical apparatus to achieve both excellent cycle performance and safety performance. Selectively, S2 / S1 is within the range of 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, or any two of the above values. Furthermore, in some embodiments, the condition 0.7 ≤ S2 / S1 ≤ 1.3 is satisfied. In this case, the cycle performance and safety performance of the electrochemical apparatus are even better.
[0036] In some embodiments, the first positive electrode active material has a layered crystalline structure belonging to the R-3m space group. In some embodiments, the first positive electrode active material is Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1 The set includes the following values: 0.6≦x1≦1.2, 0.001≦m≦0.15, 0.3≦y1≦0.7, 0.3≦z1≦0.7, 0≦q1≦0.2, and 0≦n1≦0.2. Here, element M1 includes at least one of Na or K. Element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge. Also, element T1 includes at least one of F, Cl, Br, I, or N.
[0037] In some embodiments, the second positive electrode active material has a layered crystalline structure belonging to the R-3m space group. In some embodiments, the second positive electrode active material is Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2 The following conditions apply: 0.6≦x2≦1.2, 0.8≦y2≦0.98, 0.01≦z2≦0.19, 0.01≦p≦0.19, 0≦q2≦0.1, and 0≦n2≦0.2. Here, element M2 contains at least one of Mn or Al. Element R2 contains at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge. Also, element T2 contains at least one of F, Cl, Br, I, or N.
[0038] In some embodiments, the positive electrode piece may further include a positive electrode current collector, in which case the positive electrode active material layer may be located on one or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may include aluminum foil. Of course, other positive electrode current collectors commonly used in the art may be used. In some embodiments, the thickness of the positive electrode current collector is 7 μm to 20 μm.
[0039] In some examples, the positive electrode active material layer may further contain a conductive agent and a binder. In some examples, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, or carbon nanofibers. In some examples, the binder includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylic acid ester copolymer, polyamide, polyacrylonitrile, acrylic acid ester polymer, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. In some examples, the mass ratio of the positive electrode active material, conductive agent, and binder in the positive electrode active material layer is (90-99):(0.1-10):(0.1-10), but this is merely an example, and any other suitable mass ratio may be adopted.
[0040] In some embodiments, the electrochemical apparatus further includes a negative electrode piece and a separator, wherein the positive electrode piece and the negative electrode piece are separated by a separator placed between them. In some embodiments, the negative electrode piece includes a negative electrode current collector and a negative electrode active material layer. In some embodiments, the negative electrode active material layer may be provided on one or both sides of the negative electrode current collector.
[0041] In some embodiments, the negative electrode active material layer may include a negative electrode active material, a binder, and optionally a conductive agent. In some embodiments, the negative electrode active material may include at least one of carbon materials or silicon-based materials. In some embodiments, the carbon material includes at least one of graphite, hard carbon, soft carbon, or mesocarbon microbeads. In some embodiments, the silicon-based material includes at least one of silicon, silicon oxide materials, silicon-carbon materials, or silicon oxide-carbon materials.
[0042] In some embodiments, the binder in the negative electrode active material layer may include at least one of carboxymethylcellulose sodium (CMC), polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyimide, polysiloxane, styrene-butadiene rubber, urethane resin, or acrylic ester polymer. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjenblack, carbon nanotubes, graphene, or carbon nanofibers. In some embodiments, the mass ratio of the negative electrode active material, conductive agent, and binder in the negative electrode active material layer can be (78-98.5):(0.1-10):(0.1-10). The above is merely an example, and it should be understood that any other suitable materials and mass ratios can be adopted. In some embodiments, the negative electrode current collector can be at least one of copper foil, nickel foil, or carbon-based current collector.
[0043] In some examples, the separator includes a porous substrate layer and a heat-resistant layer. In some examples, the porous substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide, or aramid. In some examples, the thickness of the separator is in the range of 3 μm to 20 μm. In some examples, the pore diameter of the porous substrate layer is in the range of 0.01 μm to 1 μm.
[0044] In some embodiments, the heat-resistant layer comprises inorganic particles and a binder. The inorganic particles are at least one selected from the group consisting of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium oxide (HfO2), tin oxide (SnO2), cerium oxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder for the heat-resistant layer is at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, acrylic acid ester polymer, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene.
[0045] In some embodiments, the electrochemical apparatus includes a lithium-ion battery, but this application is not limited thereto.
[0046] In some examples, the electrochemical apparatus further comprises an electrolyte containing a lithium salt and a non-aqueous solvent. In some examples, the lithium salt contains lithium hexafluoride phosphate. In some examples, the concentration of the lithium salt is 1 mol / L to 2 mol / L. In some examples, the non-aqueous solvent may be a carbonate ester compound, a carboxylic acid ester compound, an ether compound, or a combination thereof.
[0047] In some examples, the carbonate ester compound may be a linear carbonate ester compound, a cyclic carbonate ester compound, or a combination thereof. Examples of linear carbonate ester compounds include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methylethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate ester compounds include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), or combinations thereof. Examples of carboxylic acid ester compounds include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone, methyl formate, or combinations thereof. Examples of ether compounds include dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or combinations thereof.
[0048] A second aspect of the present application further provides an electronic device including the electrochemical device described above. The electronic devices of the embodiments of the present application are not particularly limited and can be used as any electronic device known in the prior art. In some embodiments, the electronic devices may include, but are not limited to, notebook computers, pen-input computers, mobile computers, e-book players, mobile phones, portable fax machines, portable copiers, portable printers, headphone stereos, video recorders, LCD televisions, handheld vacuum cleaners, portable CD players, MiniDiscs, transceivers, electronic organizers, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric assist bicycles, bicycles, unmanned aerial vehicles, lighting fixtures, toys, game consoles, clocks, power tools, flashes, cameras, large household storage batteries, lithium-ion capacitors, and the like.
[0049] In the following, using lithium-ion batteries as an example, several specific examples and comparative examples are given to better explain the present invention. Example 1
[0050] Preparation of negative electrode pieces: Artificial graphite, styrene-butadiene rubber, and sodium carboxymethylcellulose are mixed in a mass ratio of 96:2:2, then dispersed in deionized water to prepare a negative electrode slurry with a solid content of 0.8. After uniform stirring, the negative electrode slurry is uniformly applied to one surface of a copper foil, which is the negative electrode current collector, and dried at 80°C to obtain a negative electrode piece with a negative electrode active material layer applied to one side. The above process is repeated on the other surface of the copper foil to obtain a negative electrode piece with a negative electrode active material layer applied to both sides, and then cold rolling, cutting, and tab welding are performed to obtain the negative electrode piece.
[0051] Preparation of positive electrode pieces: Positive electrode active material (including first and second positive electrode active materials, with the mixed mass ratio shown in Table 1), conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are mixed in a mass ratio of 93.7:2.8:1.2:2.3, then dispersed in N-methylpyrrolidone to prepare a positive electrode slurry with a solid content of 0.7. After thorough stirring and mixing, the positive electrode slurry is uniformly applied to one surface of an aluminum foil, which is the positive electrode current collector, and dried at 85°C to obtain a positive electrode piece with a positive electrode active material layer applied to one side. The above process is repeated on the other surface of the aluminum foil to obtain a positive electrode piece with positive electrode active material layers applied to both sides, and then cold rolling, cutting, and tab welding are performed to obtain the positive electrode piece.
[0052] The process for preparing the first positive electrode active material is as follows: 1) Based on the elemental molar ratio Ni:Mn=50:50, a mixed solution containing NiSO4 and MnSO4 is prepared and reacted with a precipitating agent (NaOH solution) and a complexing agent (ammonia water). The reaction time is controlled to 60 hours, ammonia concentration of 1 mol / L, and pH value of 12.2 to obtain nickel-manganese precursor TM(OH)2 (TM=Ni / Mn) with an average particle size Dv50 of 11 μm. 2) The nickel-manganese precursor and sodium carbonate are uniformly polished and mixed in a ratio of Na:(Ni+Mn) molar ratio of 1.05:1. After firing in an air atmosphere at 800°C for 20 hours, the mixture is crushed, sieved, and demagnetized to obtain product 1. 3) Mix product 1 with a mixture of lithium hydroxide and lithium nitrate (molar ratio 1:1). The mass ratio of the mixture of lithium hydroxide and lithium nitrate to product 1 is 10:1. Heat to 400°C at a heating rate of 10°C / min, hold for 6 hours, then rapidly cool to room temperature at a cooling rate of 50°C / min with a mixed gas of Ar and air (volume ratio of Ar to air = 1:2) to obtain product 2. 4) Wash product 2 in deionized water, then dry it. 5) Finally, the first positive electrode active material is obtained by crushing and sieving. The first positive electrode active material has a Na / (Ni+Mn) molar ratio of 10.7% and a Dv50 of 9.4 μm.
[0053] The second positive electrode active material is a single-crystal high-nickel ternary material LiNi with a Dv50 of 4.8 μm. 0.9 Co 0.06 Mn 0.04 Use O2.
[0054] Separator fabrication: A porous polyethylene (PE) film with a thickness of 8 μm is used as the separator.
[0055] Preparation of electrolyte: In a glove box under an argon atmosphere with a moisture content of less than 10 ppm, lithium hexafluoride phosphate and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): propyl propionate (PP): ethyl propionate (EP) = 1:1:1:1:1, by weight ratio) are uniformly mixed to prepare the electrolyte. Here, the mass percentage of lithium hexafluoride phosphate in the electrolyte is 12.5%.
[0056] Lithium-ion battery fabrication: A positive electrode piece, a separator, and a negative electrode piece are stacked in order, with the separator positioned between the positive and negative electrode pieces for insulation, and then wound to obtain an electrode assembly. The electrode assembly is placed inside an aluminum laminate film for exterior use, dehydrated at 80°C, and then the electrolyte is injected and sealed. A lithium-ion battery is obtained through processes such as chemical conversion, degassing, and shaping.
[0057] Examples 2 to 13 differ from Example 1 in that the composition of the positive electrode active material was adjusted to the mixed mass ratio of the first positive electrode active material and the second positive electrode active material shown in Table 1.
[0058] Comparative Example 1 differs from Example 1 in that it uses only the first positive electrode active material as the positive electrode active material.
[0059] Comparative Example 2 differs from Example 1 in that it uses only the second positive electrode active material as the positive electrode active material.
[0060] Furthermore, in this application, the corresponding parameters are measured using the following method. 1) Peak area In the voltage range of 2.8V to 4.35V, a lithium-ion battery is charged and discharged with a current of 0.1C. A relationship curve between the capacitance-voltage derivative dQ / dV during discharge and the voltage V is obtained, and the peak area of each corresponding peak is calculated by integrating over each peak in the curve. Here, two peaks that partially overlap are separated by the inflection point where the two peaks connect. 2) Particle morphology, average diameter and area ratio S2 / S1 The positive electrode piece is cut longitudinally by ion milling, and then the morphology of the positive electrode active material particles in the cross-section of the positive electrode piece is observed using a scanning electron microscope (instrument model: ZEISS SEM, acceleration voltage: 0.1KV~30KV). In the cross-sectional image, 50 particles of either the first or second positive electrode active material are randomly selected, and the average of their longest diameters is taken as the average diameter of the first or second positive electrode active material. In the cross-sectional image, a region of 127 μm × 34 μm is randomly selected, and the area of the first positive electrode active material and the area of the second positive electrode active material within that region are measured using image software, with S1 being the area and S2 being the area of the second positive electrode active material, and the area ratio S2 / S1 is calculated accordingly. 3) Elemental content For the initial positive electrode active material, the first and second positive electrode active materials are dissolved in a mixed solvent (for example, a mixed solvent consisting of 10 ml of aqua regia (a 1:1 mixture of nitric acid and hydrochloric acid) and 2 ml of HF is used for 0.4 g of positive electrode active material), the volume is adjusted to 100 mL, and the content of each element in the solution is measured using an ICP analyzer. For the first and second positive electrode active materials contained in the positive electrode piece, the positive electrode piece is cut longitudinally by ion milling, and then the cross-section of the positive electrode piece is observed using a scanning electron microscope (instrument model: ZEISS SEM). The first and second positive electrode active materials are then measured using an energy-dispersive X-ray spectrometer (EDS), and the elemental content of the first and second positive electrode active materials is determined. 4) X-ray diffraction A lithium-ion battery is completely discharged and disassembled to obtain a positive electrode piece. X-ray diffraction analysis is then performed on the positive electrode piece using an X-ray diffractometer (model: Bruker D8 ADVANCE, target: Cu Kα, scanning angle: 5-80°). 5) Discharge capacity test per gram A lithium-ion battery is first charged with a constant current of 0.5C at a constant temperature of 25°C until it reaches 4.35V. Then, it is charged with a constant voltage until the current drops to 0.05C, and finally, it is discharged with a constant current of 0.2C until it reaches 2.8V. Discharge capacity per gram = Discharge capacity at 0.2C / Mass of positive electrode active material. 6) Cycle performance test First, the initial charge and discharge cycle was performed in a 45°C environment. Constant current charging was performed at 0.5C until the voltage reached 4.35V, then constant voltage charging was performed until the current reached 0.05C, and finally, constant current discharge was performed at 0.5C until the voltage reached 2.8V. The above charge and discharge cycle was repeated, and the discharge capacity at the 3rd cycle and the 500th cycle were recorded. 45°C cycle capacity retention rate = (Discharge capacity at the 500th cycle / Discharge capacity at the 3rd cycle) × 100%. 7) Pass rate of nail-piercing The lithium-ion battery is charged with a constant current at a rate of 0.5C until the voltage reaches 4.35V, then charged with a constant voltage at 4.35V until the current reaches 0.05C, bringing the lithium-ion battery to a fully charged state. The appearance of the lithium-ion battery before testing is recorded. A nail puncture test will be performed on the batteries in an environment of 25±3℃. The diameter of the steel nail will be 4 mm, the puncture speed will be 30 mm / s, and the puncture point will be the geometric center of the lithium-ion battery. The test will be conducted for 3.5 minutes or stopped after the battery surface temperature has dropped to 50℃. Ten lithium-ion batteries will be used as one group, and the state of the lithium-ion batteries will be observed during the test. The test will be considered passed if the lithium-ion battery does not burn or explode. The nail puncture pass rate = number of successful batteries / 10 8) Hotbox exam pass rate A hot box test will be conducted using 10 lithium-ion batteries. The lithium-ion batteries will be charged with a constant current of 0.5C until the voltage reaches 4.35V, and then charged with a constant voltage of 0.05C at 4.35V until the current reaches 0.05C, bringing the lithium-ion batteries to a fully charged state. The fully charged lithium-ion batteries will be placed in a test box, and the test box will be heated at a rate of 5°C / min. After the box temperature reaches (150±2)°C, it will be maintained at a constant temperature for 60 minutes. The test will be considered passed if the lithium-ion batteries do not ignite or explode. Hot box test pass rate = number of successful batteries / 10.
[0061] Table 1 shows the parameters and evaluation results for Examples 1-13 and Comparative Examples 1-2.
[0062] [Table 1]
[0063] As is clear from the comparison between Examples 1-13 and Comparative Example 2, the pass rates for both the nail penetration test and the hot box test of the lithium-ion batteries in Examples 1-13 are significantly improved compared to Comparative Example 2, which does not use the first positive electrode active material, which is advantageous for improving the safety performance of lithium-ion batteries.
[0064] As is clear from the comparison between Examples 1-13 and Comparative Example 1, the discharge capacity per gram and cycle capacity retention rate of the lithium-ion batteries in Examples 1-13 are significantly improved compared to Comparative Example 1, which does not use a second positive electrode active material.
[0065] Furthermore, as is clear from the comparison of Examples 1 to 13, 0.5 ≤ S B / S A When the ratio is ≤0.85 or 2.3 ≤ P2 / P1 ≤ 6.5, the cycle capacity retention rate, nail penetration test pass rate, and hot box test pass rate of lithium-ion batteries are all superior. Also, when the ratio is ≤0.75 ≤ S2 / S1 ≤ 1.3, the cycle capacity retention rate, nail penetration test pass rate, and hot box test pass rate of lithium-ion batteries are all superior.
[0066] The foregoing are merely preferred embodiments of the present application and do not limit the scope of protection. All modifications, equivalents, improvements, etc., made within the spirit and principles of this application are included within the scope of protection.
Claims
1. An electrochemical apparatus comprising a positive electrode piece containing a positive electrode active material layer, The positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material comprises Ni and Mn elements. The second positive electrode active material comprises Ni and Co. An electrochemical apparatus characterized in that the relationship curve between the capacitance voltage derivative dQ / dV and the voltage V during discharge of the electrochemical apparatus contains at least two peaks at 3.8V or higher.
2. The relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus includes peaks A and B at 3.8V and above. The peak position of the aforementioned peak A is in the range of 3.8V to 4.1V. The peak position of peak B is in the range of 4.1V to 4.3V. The peak area of the aforementioned peak A is S A The peak area of peak B is S B Therefore, 0.5 ≤ S B / S A The condition ≤ 1 is satisfied, and preferably 0.5 ≤ S. B / S A The electrochemical apparatus according to claim 1, characterized in that it satisfies ≤0.
85.
3. The electrochemical apparatus is, (1) The relationship curve between the capacitance voltage derivative dQ / dV and voltage V during discharge of the electrochemical apparatus further includes a peak C in the range of 3.5V to 3.7V, (2) The relationship curve between the capacitance voltage derivative dQ / dV and the voltage V during discharge of the electrochemical apparatus contains at least one peak at 4.1V or higher. The electrochemical apparatus according to claim 1, characterized in that it satisfies at least one of the following conditions.
4. When the electrochemical device is in a fully discharged state, and X-ray diffraction measurement is performed on the positive electrode plate, it has a diffraction peak 1 in the range of 43.7° to 44.1°, and the peak intensity of the diffraction peak 1 is defined as P 1 , it has a diffraction peak 2 in the range of 44.2° to 44.6°, and the peak intensity of the diffraction peak 2 is defined as P 2 , then 1 ≦ P 2 / P 1 ≦6.5 is satisfied, the electrochemical device according to claim 1.
5. 2.3 ≤ P 2 / P 1 The electrochemical apparatus according to claim 4, characterized in that it satisfies ≤ 6.
5.
6. The electrochemical apparatus is, (1) The first positive electrode active material further contains element M1, where M1 contains at least one of Na or K, and based on the metal elements other than Li and M1 in the first positive electrode active material, if a1 is the molar percentage of Ni in the first positive electrode active material, b1 is the molar percentage of Mn, and c1 is the molar percentage of M1, then the following conditions are met: 30% ≤ a1 ≤ 70%, 30% ≤ b1 ≤ 70%, and 0.1% ≤ c1 ≤ 15%. (2) The second positive electrode active material further contains element M2, where M2 contains at least one of Mn or Al, and based on the metal elements other than Li in the second positive electrode active material, if a2 is the molar percentage of Ni in the second positive electrode active material, b2 is the molar percentage of Co, and c2 is the molar percentage of M2, then the following conditions are met: 80% ≤ a2 ≤ 98%, 1% ≤ b2 ≤ 19%, and 1% ≤ c2 ≤ 19%. (3) The first positive electrode active material is Li x1 M1 m Ni y1 Mn z1 R1 q1 O 2±n1 T1 n1 The following conditions apply: 0.6 ≤ x1 ≤ 1.2, 0.001 ≤ m ≤ 0.15, 0.3 ≤ y1 ≤ 0.7, 0.3 ≤ z1 ≤ 0.7, 0 ≤ q1 ≤ 0.2, 0 ≤ n1 ≤ 0.2, where element M1 includes at least one of Na or K, element R1 includes at least one of Co, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge, and element T1 includes at least one of F, Cl, Br, I, or N. (4) The second positive electrode active material is Li x2 Ni y2 Co z2 M2 p R2 q2 O 2±n2 T2 n2 The equation includes 0.6 ≤ x² ≤ 1.2, 0.8 ≤ y² ≤ 0.98, 0.01 ≤ z² ≤ 0.19, 0.01 ≤ p ≤ 0.19, 0 ≤ q² ≤ 0.1, and 0 ≤ n² ≤ 0.2, where element M² includes at least one of Mn or Al, element R² includes at least one of Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Na, K, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge, and element T² includes at least one of F, Cl, Br, I, or N. The electrochemical apparatus according to claim 1, characterized in that it satisfies at least one of the following conditions.
7. The electrochemical apparatus is, (1) The first positive electrode active material is a secondary particle formed by the aggregation of primary particles, (2) The average particle size of the first positive electrode active material is 6 μm to 14 μm, (3) The above second positive electrode active material is a primary particle, (4) The average particle size of the second positive electrode active material is 3 μm to 10 μm, The electrochemical apparatus according to claim 1, characterized in that it satisfies at least one of the following conditions.
8. In the cross-section in the thickness direction of the positive electrode active material layer, the area of the first positive electrode active material in a region of 127 μm × 34 μm is S. 1 , the area of the second positive electrode active material is S 2 Therefore, 0.5 ≤ S 2 / S 1 The electrochemical apparatus according to claim 1, characterized in that it satisfies ≤ 1.
5.
9. 0.75 ≤ S 2 / S 1 The electrochemical apparatus according to claim 8, characterized in that it satisfies ≤ 1.
3.
10. An electronic apparatus characterized by including the electrochemical apparatus described in any one of claims 1 to 9.